Mother's breast milk supplemented with donor milk reduces hospital and health service usage costs in low-birthweight infants. (September 2016) - Dritsakou, Kalliopi; Liosis, Georgios; Valsami, Georgia; Polychronopoulos, Evangelos; Souliotis, Kyriakos; Skouroliakou, Maria
Abstract: Objective: to compare hospital and health service usage costs of feeding low-birthweight (LBW) infants predominantly with their mother's milk, supplemented with donor milk, with donor milk and preterm formula. Design: prospective matching study. Setting: tertiary public perinatal centre, neonatal intensive care unit (NICU) and donor human milk bank. Participants: 100 LBW infants (Group I) fed predominantly with their mother's milk from the first hour of life, supplemented (mainly for the first week of life) with donor milk, were matched on a 1:1 basis with 100 LBW infants (Group II) who were fed with donor milk for the first 3 weeks of life followed by preterm formula until hospital discharge. Individualised targeted fortification of human milk was implemented in both study groups. Findings: the costs of hospitalisation, doctor visits and prescription drugs for viral infections until 8 months of age were calculated for each infant. Infants fed predominantly with their mother's milk had significantly shorter hospital stays and lower hospitalisation costs. In Group I infants, the duration of enteral gavage feeding was shorter, resulting in significantly lower costs. Up to 8 months of age, Group I infants experienced fewer episodes of viral infections, and the cost of each doctor visit and drug prescription was lower for these infants. Conclusions: feeding LBW infants predominantly with their mother's milk reduces hospital and health service usage costs. Implications for practice: feeding LBW infants predominantly with their mother's milk, supplemented with donor milk, followed by exclusive breast feeding seems to result in potential savings in hospital and health service usage costs. Highlights: Feeding LBW infants predominantly with their mother's own milk, supplemented with donor milk, and followed by exclusive breast feeding, in NICU, seems to result in potential savings in hospital and health services use cost. The establishment of human milk banks and the certification of maternity hospitals as infant friendly, reduce hospitalisation cost. A LBW infant exclusively breast feeding suffers fewer episodes of viral infections, after hospital discharge, while less money per each doctor visit and drug prescription for a viral infection is spent.